El Uso de alcohol como combustible en motores de combustión interna (Revista Cientifica Ingenio Magno, 2023)
The use of renewable biofuels can play a leading role in energy security, as well as in reducing dependence on oil, which is, by the way, running out. Among liquid biofuels is alcohol whose composition and properties will depend on the raw materials and the conditions of their processing, for this there are two ways to obtain alcohol in its application in internal combustion engine, either chemically or biologically. As for their production, it is expected that as demand for alcohols increases, the cost will become more competitive. Bioalcohols can be applied in gasoline engine either in mixture or with additives, its use obtains some benefits as the generation of cleaner combustion producing less CO and NOx, in the case of diesel engine alcohol can be applied in various ways as fumigation, dual combustion, in mixture of alcohol with diesel and as emulsion. Finally, HCCI engines have a great ability to burn multiple fuels with various physical and chemical properties, so they are natural candidates to apply them with bioalcohols.
Keywords: Alcohol, engine, production methods, emissions